THE TRANSLATION, VALIDATION AND CULTURAL ADAPTATION OF FUNCTIONAL ASSESSMENT OF CHRONIC ILLNESS THERAPY - SPIRITUAL WELL-BEING 12 (FACIT-SP12) SCALE IN GREEK LANGUAGE - Fradelos, Evangelos C. (Mater Sociomed, 2016)
BACKGROUND: According to World Health Organization (WHO), spirituality is an important domain of quality of life especially in terminal, life threatens chronic diseases. For many people spirituality and religion are not just very important dimensions of their existence, but also a source of support that contributes to wellbeing and coping with everyday difficulties of life. AIM: Aim of the study was the translation of the Facit Spiritual Well Being Scale (Facit-Sp12) in Greek language and the validation of the scale for the Greek population. MATERIAL AND METHODS: The Facit-Sp12 questionnaire is an anonymous self-administered questionnaire that contains twelve, four point Likert scale, closed questions (0=Not at all, 1=A little bit, 2=Some-what, 3=Quite a bit, 4=Very Much). The questionnaire was translated into Greek language and then back translated in the English in order to be checked for any inconsistencies. The sample of the study was 183 chronic kidney disease patients, undergoing hemodialysis. Exploratory factor analysis, with principal components analysis with Varimax rotation was performed for checking the construct validity of the questionnaire. The test–retest reliability and the internal consistency were also examined. Statistical analysis performed by the use of SPSS 21.0. Statistical significance level was set at p=0.05 RESULTS: The final Greek version of the questionnaire includes all of the twelve questions. The mean age of the participants was 61.81±13.9. Three factors were exported from the statistical analysis. The Cronbach-α coefficient was 0.77 for the total questionnaire and for each subscale was 0.70 for “meaning”, 0.73 for “peace” and 0.87 for “faith”. Between the three subscales “meaning” had the highest score (mean 12.49, SD=2.865). CONCLUSIONS: The Facit Spiritual Wellbeing Scale–Facit-Sp12, is a valuable and reliable questionnaire of three dimensions that can be used for assessing spirituality and spiritual wellbeing in Greek population.